Ion Pairs between Maleonitriledithiolato Complex Dianions of Cobalt and Nickel and Macrocyclic Ligand Complex Dications of Nickel(II) - Control of Intrapair Interaction through Ligand Modification - Kisch, Horst; Nowicka, B.; Schmauch, G.; Chihara, T.; Heinemann, Frank Wilhelm; Hagiwara, M.; Wakatsuki, Y. (Bulletin of the Chemical Society of Japan, 2002)
The ion pairs [Ni(cyclam)] 2+[M(mnt) 2] 2- (M = Co, Ni: 1a,b), [Ni(tmc)] 2+[M(mnt) 2] 2- (M = Co, Ni: 2a,b) and the solvent complexes [Ni(cyclam)(dmso) 2] 2+ [M(mnt) 2] 2- (M = Co, Ni, mnt 2- = maleonitriledithiolato = (Z)1,2-dicyano-1,2-ethylenedithiolato, cyclam = 1,4,8,11-tetraazacyclotetradecane, tmc = 1,4,8,11-tetramethyl-1,4,8,11-tetraazacyclotetradecane) were isolated and structurally characterised. The nature of the macrocyclic ligand and the presence of coordinating solvents determine whether the dication is present as a tetra-, penta- or hexacoordinated complex. In 1a the tetracoordinated dications and dianions are arranged in a mixed stack structure; the absences of any short contacts and of a mutual ion pair charge transfer band indicate the absence of charge transfer interaction. The highly puckered cyclam ligand will prevent a close approach of the planar bis(maleonitriledithiolato)cobaltate(II). When cyclam is replaced by its tetramethyl derivative tmc, a strong coordinative interaction is introduced as indicated by the structure of 2a. One dianion coordinates to two dications through two trans-cyano groups. The resulting trinuclear dications [Ni(tmc)][Co(mnt) 2][Ni(tmc)] 2+ form segregated columns separated by the non-interacting, remaining dianion. Crystallisation in the presence of a coordinating solvent like dimethyl sulfoxide (dmso) leads to the ion pairs [Ni(cyclam)(dmso) 2] 2+ [M(mnt) 2] 2-containing hexacoordinated dications. Magnetic susceptibility measurements at room temperature are in accord with the observed structures. While 1b is diamagnetic, 1a, 2a, 2b, and the two solvent complexes exhibit values characteristic of the isolated ions, in agreement with the absence of any electronic interaction between dication and dianion within the ion pair. Temperature-dependent measurements down to 1.7 K indicate that a weak antiferromagnetic interaction is present in 2a.
UnivIS-Import:2017-03-24:Pub.2002.nat.dchph.paoc24.ionpai